Draft Five Year Plan 1978-83 Volume-II - Planning Commission (Planning Commission, 1978)
Head of Development—Outlay and Expenditure Draft Plan 1978-83—Minor Heads—Outlay and Expenditure Phasing of Financial Outlay for 1978-83—Scheme-wise Crop Production: Achievements and Targets Crop Production - Targets of Terminal Years Selected Programmes: Achievements and Targets. Minor Irrigation Programmes—Achievements and Targets Forestry Programmes—Achievements and Targets Rural Development Achievement and Selected Physical Targets and Programmes Fisheries Targets of Production and Selected Physical Programme
State Planning Board Trivandrum